UMPSA strengthens global strategic collaboration at the Higher Education Forum between Government of Malaysia and Republic of Uzbekistan - Mohd Ferdaus, Musa (UMPSA, 2025)
TANJUNG MALIM, 4 February 2025 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) continues to expand its global strategic network by forging new collaborations at the Higher Education Forum Between the Government of Malaysia and the Republic of Uzbekistan, recently held at Universiti Pendidikan Sultan Idris (UPSI). The forum was jointly organised by the Ministry of Higher Education Malaysia (MOHE), the Ministry of Higher Education, Science and Innovation of Uzbekistan, and UPSI.